CIN III Diagnosed following Surgical Termination of Pregnancy - Ciara Mackenzie; Abiodun Fakokunde; Abha Govind; Delaram Kermani (Case Reports in Obstetrics and Gynecology)
We present a case of a 30-year-old mother of four who was incidentally diagnosed with cervical intraepithelial neoplasia (CIN) III following surgical termination of pregnancy. Five years previously a routine smear test had shown mild dyskaryosis but was never repeated. She was referred to colposcopy and, underwent loop excision of the transformation zone (LLETZ) and subsequently vaginal hysterectomy. Without this incidental finding she would have undoubtedly developed cervical cancer. We discuss the deficiencies in current cervical cancer prevention strategies and termination of pregnancy services. We emphasise the importance of ensuring that patients with dyskaryosis are not lost to follow-up and we consider whether there should be clearer guidance on the value of histological examination of products of conception following termination of pregnancy.